Transcriptome analysis reveals the mechanisms involved in the enhanced antagonistic efficacy of Rhodotorula mucilaginosa induced by chitosan. (May 2021) - Zhang, Xiaoyun; Gu, Ning; Zhou, You; Godana, Esa Abiso; Dhanasekaran, Solairaj; Gu, Xiangyu; Zhao, Lina; Zhang, Hongyin
Abstract: Our previous study showed that the biocontrol efficacy of Rhodotorula mucilaginosa against postharvest diseases of strawberries can be significantly enhanced by chitosan. Proteome analysis of R. mucilaginosa induced by chitosan has preliminarily explored the molecular mechanisms involved in the enhanced antagonistic efficacy of R. mucilaginosa induced by chitosan. In this study, transcriptome analysis of R. mucilaginosa cultured with and without chitosan was performed, and the activities of CAT, PPO, POD, and SOD were also investigated to further explore the involved mechanisms. The results indicated that the activities of these antioxidant enzymes in R. mucilaginosa were all significantly increased by 0.5 g/100 mL chitosan. Especially, POD activity was about 1.5 - fold higher than the control. Transcriptome and bioinformatic analysis revealed that significant number of genes involved in growth and reproduction, adhesion, energy production, oxidative stress response and other stress response were all induced by chitosan, which resulted in the enhanced antagonistic efficacy of R. mucilaginosa . These results provide a reference for the future study on controlling postharvest disease of fruit and vegetables by antagonist yeast and provide a theoretical basis for the practical application of antagonist yeast. Highlights: Chitosan induced certain genes related to growth and reproduction in R. mucilaginosa. Expression of some genes involved in energy production was enhanced. Antioxidant enzyme activities and oxidative stress response genes were induced. Expression of genes correspond to various adversity response was increased.